Performance and biological indicators of a laboratory-scale activated sludge reactor with phosphate simultaneous precipitation as affected by ferric chloride addition - de Gregorio, Carolina (2010)
Iron-base coagulants are widely used for the phosphorous removal from wastewaters. Coagulants may be applied on the secondary treatment (simultaneous precipitation); however, coagulant excess may alter the biological process. The objectives of this work were: (a) to study in a laboratory-scale activated sludge reactor, fed with a model wastewater system from the dairy industry, the feasibility of phosphorous removal by applying simultaneous precipitation using ferric chloride; (b) to assess the effect of different Fe:P (molar ratio) dose ranges: high = 1.9-2.3:1, mean = 1.5-1.9:1 and low = 1.0-1.4:1 on the reactor performance by measuring physical-chemical parameters (pH, COD, TSS, Fe, P), settling properties (DSVI, diluted sludge volume index) and abundance of filamentous microorganisms by microscopic observation; (c) to evaluate the effect of the coagulant on activated sludge microfauna (abundance and morphological-functional groups); (d) to assess the usefulness of these parameters as control tools. A high Fe:P ratio acted as shock load improving the soluble phosphorous and COD removal. Sludge settling properties were rapidly improved due to both a successful control of filamentous bulking and an increase in the flocs density. Prolonged application of high Fe(III) doses negatively affected the reactor performance; a Fe:P ratio = 1.5-1.9:1 achieved an acceptable effluent quality. Changes in the density of Chilodonella sp., Opercularia sp., Vorticella microstoma, Vorticella spp., Colpoda sp. and rotifers were analyzed as a function of the progressive enrichment of Fe(III) in the sludge. Crawling ciliates constituted the most sensitive group to changes in the activated sludge reactor environmental quality, becoming a potential biological indicator of Fe(III) overload.